The Colorado state constitution - Collins, Richard B; Oesterle, Dale A. 1950- (The Oxford commentaries on the state constitutions of the United States, 2020)
In gathering the information needed to write this book, the authors came to appreciate several themes. First, the Colorado Constitution and case law offer a novel and refreshing perspectives on the history of the state. Most major social movements, crises, embarrassments and celebrations ended up in state courts, with a constitutional argument by at least one major participant. The courts' role was often decisive and occasionally miscast in traditional histories. Second, over long stretches of time the Colorado Supreme Court's performance was less than exemplary. The original three-judge court in the 1880s launched the judicial branch very well, and the modern court is professional and conscientious. During many other periods, the court was blatantly partisan and at times, well, just zany. The court's relationship to the legislature vacillated from too little deference, such as the court's pro-business and anti-labor stance during the 1890-1920 period or the court's strange interference with relief for the poor during the Depression, to too much deference, such as the court's blessing after 1905 of numerous taxing and debt schemes pushed by the legislature to subsidize a variety of private industries. The framers' rules for the structure and processes of government, however, have held up and continue to serve. Since the 1850s this beautiful spot of geography has been witness to a turbulent, tumultuous, occasionally violent boom-and-bust style of human society that continues. For residents it has been and is life in high, unpredictable winds"--